The effect of nebulized antibiotics in children with tracheostomy - (:unkn) unknown (ELSEVIER IRELAND LTD, 2021)
Introduction: Children with tracheostomy have an increased risk of bacterial colonization and infection of the lower respiratory tracts. This study aimed to investigate the effects of nebulized antibiotics on the bacterial load, the need for oral antibiotics, the number of hospitalizations, and the length of stay in the intensive care unit in tracheotomised children with persistent colonization. Methods: Children with tracheostomy and persistent bacterial colonization who were started on nebulized antibiotic therapy after a lower respiratory tract infection were included in the study. Nebulized gentamicin or colistin were used according to the results of the tracheal aspirate cultures. Demographic and clinic characteristics were recorded from one year prior until one year after initiation of nebulized antibiotic treatment. Results: Nebulized antibiotic treatment was initiated in 22 patients. Nebulized gentamicin was administered to 14 patients (63.6%) and colistin to 8 patients (36.4%). The median duration of treatment was 3 months (range 2?5 months). Following nebulized antibiotic treatment, median number of hospitalizations decreased from 2 (range 1.0?3.5) to 1 (range 0.0?1.5) (p = 0.04). The median length of stay in the intensive care unit reduced significantly from 89.5 days (range 43.0?82.5) to 25 days (range 7.75?62.75) after starting nebulized antibiotics (p = 0.028). Following nebulized antibiotic treatment median bacterial colony count also decreased (from 105 CFU/ ml (range 105-106) to 6 ? 104 CFU/ml (range 104-105); p = 0.003). There were no significant side effects during nebulized antibiotic therapy. Conclusions: The use of nebulized antibiotics reduced the number of hospitalizations, length of stay in the intensive care unit, and bacterial load in tracheotomised children with persistent airway colonization without significant side effects. The use of nebulized antibiotics showed a statistically significant decrease in the measures studied. Use of nebulized antibiotics may help to decrease the health care burden of these children, families and health care system. Further studies are needed to determine the indications and optimal duration of long-term nebulized antibiotic treatment in children with tracheostomy.
Keywords: Children; Nebulized antibiotics; Tracheostomy; Bacterial colonization; RESPIRATORY-TRACT INFECTIONS; PSEUDOMONAS-AERUGINOSA; RISK-FACTORS; COLONIZATION; TRACHEOTOMY